Microwave Absorbing Properties of Polycrystalline La0.67Sr0.33MnO3 - Laksanawati, Wahyu Dian; Burhendi, Feli Cianda Adrin; Kusdiwelirawan, Acep (Program Studi Pendidikan Fisika UHAMKA, 2019)
Sample La_0.67Sr_0.33MnO3 has been successfully synthesized by sol gel method shown by the results of XRD formed a single phase with rhombohedral crystal structure. The results of SEM showed particles are agglomerated yet functional groups Mn-O-Mn has been formed based on the results of FTIR. The ability of the sample to absorb the microwaves still lower that the value of reflection loss obtained at -26.05 dB.